Encyclopedia Brown takes the cake! - Sobol, Donald J., 1924-; Andrews, Glenn; Ohlsson, Ib, 1935- (New York : Scholastic, 1983)
The ten-year-old detective solves "The Case of the Missing Garlic Bread" and other food-related mysteries. Includes menus and recipes for a Fourth-of-July party and other occasions.
"An Apple paperback.".
Includes index.
School Library Journal.
School Library Journal, April 2009.
6.4
3-6
Keywords: Brown, Encyclopedia (Fictitious character) -- Fiction; Cooking -- Fiction; Food -- Fiction; Mystery and detective stories; Brown, Encyclopedia (Fictional character) -- Fiction; Cooking -- Fiction; Food -- Fiction; Mystery fiction